Jacyś Francuzi wymowni – kinematografia francuska jako sztuka kreowania wizerunku narodowego .......... 267 - Styczewska, Larysa; Janik, Aleksandra (Oblicza dyplomacji, 2025)
SOME ELOQUENT FRENCHMAN: FRENCH CINEMATOGRAPHY AS THE MEANS OF CREATINGTHE NATIONAL IMAGECinema plays a more important role in shaping the image of countries on the international arena than it might seem. France is a particular master of this art. The article analyzes the influence of French cinema on the country’s diplomacy and the way it is perceived internationally. Cultural diplomacy, as an integral part of public diplomacy, promotes a country’s culture and national value abroad. In the field of cinematography, entities such as Unifrance are actively involved in the promotion of French cinema by supporting film distribution and cooperation with global markets. Their activities constitute an important element of the French government diplomatic strategy. The article will focus on discussing the role of cultural diplomacy, in particular the influence of French cinematography on the implementation of the government’s public diplomacy strategy. Exploring these aspects will show why France has perfected the art of building the country’s image by promoting its own culture.